Estimasi Panjang Jeratan Kain Rajut dengan Menggunakan Model Struktur dari Popper - Pratikno Hidayat (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
This paper aims to represent an approach to the problem of predicting the length of loop yarn on the plain knitted fabric from its structure. By using a structure model introduced by Popper, a mathematical model of a knitted fabric under zero load stress and the behaviour of the approximation of a real fabric were developed. Some factors, such as the number of course and wale per cm, yarn number and fabric structure relations were considered.Keywords: zero load stress, yarn number, course and wale per cm.